Normative Analysis of the Maqāṣid Al-Syarī‘ah Theory on Pre-Marital Women's Health Screening - Asman Asman; Mohamed Aamer (IAIN Manado, 2025)
This study discusses the urgency of premarital health checks for women from the perspective of maqāṣid al-sharīʿah by emphasizing how the values of benefit can address contemporary issues related to women's reproductive health. One of the issues raised is whether premarital checks, which in some regions are beginning to be directed as administrative requirements, have the potential to marginalize women, especially if applied asymmetrically only to prospective brides. Thus, this study formulates two main questions: (1) how does maqāṣid al-sharīʿah view premarital health checks for women? and (2) can premarital checks be categorized as a hajj necessity or even elevated to darūriyyāt under certain conditions? This study uses a qualitative method with a normative nature through a literature study approach. Data were collected from fiqh literature, contemporary fatwas, national regulations, and reproductive health studies. They were then analyzed using the maqāṣid al-sharīʿah framework, which focuses on the five main objectives of Syarī‘ah, specifically the preservation of the soul and the preservation of the nasl. The results of the study indicate that premarital health checks, especially for women, are generally categorized as hajj because they aim to preserve the soul and prevent harm after marriage. However, under certain conditions, such as the potential for transmission of genetic diseases or infectious diseases, these examinations can be elevated to the category of darūriyyāt. The study also emphasizes that the obligation of premarital checks must be applied fairly and symmetrically to men and women to avoid bias or administrative marginalization. These findings contribute to strengthening policies at the Office of Religious Affairs (KUA), the development of gender-responsive national regulations, and the development of welfare-oriented family jurisprudence.